Synthesis and Antibacterial Activity of 2-Pyrazolines and Their Related Compounds - Panchal, J.M.; Desai, K.R. (Asian Journal of Chemistry, 2010)
Substituted chalcone condenses with hydrazine hydrate in ethanol to give 2-pyrazoline. In the present note some biologically active 1-[1 '-H-5'-atyl-2'-pyrazoline]-3-( 4" -bromophenyl)-5- phenyl-2-pyrazoline and their related compounds were synthesized and characterized.